1996
DOI: 10.1152/ajpgi.1996.271.6.g1003
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological characterization of a motilin agonist, GM611, on rabbit duodenal smooth muscle

Abstract: Effects of motilin and a newly synthesized erythromycin derivative, GM611, on membrane potential and currents of rabbit duodenal smooth muscle have been investigated by intracellular potential recording and whole cell patch-clamp technique and compared with results from contractile experiments. Motilin and GM611 (0.01-100 nM) dose dependently produced slowly sustained depolarizations (half-maximal effective dose = 0.15 and 3.9 nM for motilin and GM611, respectively) but exhibited biphasic effects on spike acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 0 publications
4
15
0
Order By: Relevance
“…This also indicates that the action of mitemcinal, as well as motilin, is not mediated by neural activities but by directly mediated effects on intestinal smooth muscle motilin receptors in rabbits. These findings are consistent with previous reports [12,13,23,24] in which, by experiments in the isolated rabbit small intestine, the contractile response to pMTL or some EMA derivatives was found not to be affected by TTX, atropine, hexamethonium, mepyramine (H 1 blockade), naloxone or CP-99994 (NK 1 blockade). These results suggested that contractions evoked by pMTL or EMA derivatives in the isolated rabbit small intestine are directly mediated through motilin receptors on smooth muscle cells, not by the intramural nervous system or by muscarinic, nicotinic, histamine, opiate or neurokinin receptors.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This also indicates that the action of mitemcinal, as well as motilin, is not mediated by neural activities but by directly mediated effects on intestinal smooth muscle motilin receptors in rabbits. These findings are consistent with previous reports [12,13,23,24] in which, by experiments in the isolated rabbit small intestine, the contractile response to pMTL or some EMA derivatives was found not to be affected by TTX, atropine, hexamethonium, mepyramine (H 1 blockade), naloxone or CP-99994 (NK 1 blockade). These results suggested that contractions evoked by pMTL or EMA derivatives in the isolated rabbit small intestine are directly mediated through motilin receptors on smooth muscle cells, not by the intramural nervous system or by muscarinic, nicotinic, histamine, opiate or neurokinin receptors.…”
Section: Discussionsupporting
confidence: 93%
“…The EC 50 values of mitemcinal and pMTL in the present study were 14.33 8 2.55 nmol/l (n = 6) and 4.33 8 0.43 nmol/ l (n = 10). The result is consistent with the previous report [13] that both of mitemcinal and pMTL induced the dosedependent tonic contraction in the rabbit duodenal muscle strip with EC 50 values 11.9 nmol/l for mitemcinal and 3.0 nmol/l for pMTL, respectively. The selective motilin antagonist, GM-109, shifted the concentration-dependent curves for mitemcinal and pMTL right in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations